UNHEARD VOICES: A Study on the Perceptions of Tribal School Drop-outs in Kerala - Seetha Kakkoth
This study is an enquiry into the subjective experiences of the Ashram school drop-outs of Cholanaicken and Kattunayakan (including Pathinaicken) tribes of Nilambur forests, Kerala, South India. Ashram schools are residential schools established in India, as per the recommendation by the Dhebar Commission and the National Policy on Education (NPE), exclusively for Particularly Vulnerable Tribal Groups (PTGs) for their educational advancement. It is significant to note that even after providing all infrastructural facilities and educational inputs, drop out of children from these schools is a common phenomena. In this context, the study concentrates on the issues of drop-out children from one of the two Ashram Schools in Kerala viz., Indira Gandhi Memorial Model Residential School, Nilambur, Malappuram district. It focuses on the essence/spirit of the drop-out children‘s voices and those of their parents, friends and social functionaries; and juxtaposing them against the narratives of the officials and staff with whom they have close everyday contact in the school system. Upon analyzing the issues, certain suggestive measures for the improvement of Ashram school were arrived at and are given along with the concluding remarks.